Dense SiC ceramics prepared by using amorphous sintering additives. Issue 11 (1st June 2022) - Liu, Yang; Yuan, Jin-Hao; Tian, Hou-Liang; Guo, Wei-Ming; Sun, Shi-Kuan; Duan, Xiao-Ming; Jia, De-Chang; Lin, Hua-Tay
Abstract: Spark plasma sintered SiC-based ceramics with amorphous Y2 O3 –Al2 O3 –SiO2 and CaO–Al2 O3 sintering additives prepared by melt-quench approach, were compared with those with the direct addition of raw Y2 O3 –Al2 O3 –SiO2 and CaO–Al2 O3 mixture. The relative densities of SiC-based with raw Y2 O3 –Al2 O3 –SiO2 and CaO–Al2 O3 were 95.3% and 94.3%, respectively. In spite of the same composition of sintering additive, the relative densities of SiC-based ceramics reached the values of 98.9% and 99.5% by using the glassy additives of Y2 O3 –Al2 O3 –SiO2 and CaO–Al2 O3, respectively, and the hardness of SiC-based ceramics was improved by about 22.2% and 17.2%, respectively. The amorphous sintering additive effectively improved the densification and hardness of SiC ceramics.